Birth - Glazer, Jonathan; Kidman, Nicole; Bacall, Lauren, 1924-; Bright, Cameron, 1993-; Huston, Danny, 1962-; Howard, Arliss; Heche, Anne.; New Line Cinema Corporation; Fine Line Features ([United States] : New Line Home Entertainment, 2005)
A widow for ten years, Anna is looking forward to getting remarried when a mysterious boy appears claiming to be the reincarnation of her late husband.
English track: Dolby digital 5.1; Dolby digital 2.0 stereo.
Originally released as a motion picture in 2004.
Producers, Jean-Louis Piel, Nick Morris, Lizie Gower ; writers, Jean-Claude Carriere, Milo Addica, Jonathan Glazer ; director, Jonathan Glazer ; director of photography, Harris Savides ; editor, Sam Sneade, Claus Wehlisch ; music, Alexandre Desplat ; production designer, Kevin thompson ; costume designer, John Dunn.
Nicole Kidman, Lauren Bacall, Cameron Bright, Danny Huston, Arliss Howard, Peter Stormare, Ted Levine, Anne Heche.
MPAA rating: R; for sexuality.
DVD.
Keywords: Man-woman relationships -- Drama; Reincarnation -- Drama; Feature films; Video recordings for the hearing impaired